Autoimmune Pancreatitis Can Transform Into Chronic Features Similar to Advanced Chronic Pancreatitis With Functional Insufficiency Following Severe Calcification. Issue 8 (September 2016) - Kanai, Keita; Maruyama, Masahiro; Kameko, Fumiko; Kawasaki, Kenji; Asano, Junpei; Oguchi, Takaya; Watanabe, Takayuki; Ito, Tetsuya; Muraki, Takashi; Hamano, Hideaki; Matsumoto, Akihiro; Arakura, Norikazu; et al.
Abstract : Objectives: Because several studies for autoimmune pancreatitis (AIP) have revealed pancreatic calcification resembling that in chronic pancreatitis (CP), we sought to clarify whether AIP could transform into chronic features similar to advanced CP with severe pancreatic dysfunction. Methods: Pancreatic functions of 92 AIP patients, 47 definite CP patients, and 30 healthy controls were assessed by fecal elastase-1 concentration (FEC), fasting immunoreactive insulin (IRI), and homeostatic model assessment (HOMA)-R. Results: The 92 AIP patients included 17 (18%) with severe calcification (SC) and 75 without. The FEC levels in AIP and CP patients were significantly lower than that in controls. Exocrine insufficiency defined as FEC less than 200 μg/g was 39% in AIP without SC, 56% in AIP with SC, and 74% in CP. Fasting IRI and C-peptide reactivity values in CP were significantly lower than those in AIP, with no significant differences between AIP subgroups. The prevalence of endocrine insufficiency according to fasting IRI less than 5.0 μU/mL was 26% in AIP without SC, 31% in AIP with SC, and 59% in CP, respectively. HOMA-R values were significantly higher in all AIP groups than in CP. Conclusions: Autoimmune pancreatitis can transform into a state of pancreatic insufficiency after calcification that is less severe than that in definite CP.